An assessment of Makerere University College of Health Sciences: optimizing health research capacity to meet Uganda’s priorities - Nankinga, Ziadah; Kutyabami, Paul; Kibuule, Dan; Kalyango, Joan; Groves, Sara; Bollinger, Robert C.; Obua, Celestino (BMC International Health and Human Rights, 2011)
Health research is critical to the institutional mission of the Makerere College of Health Sciences (MakCHS). Optimizing the alignment of health research capacity at MakCHS with the health needs and priorities of Uganda, as outlined in the country’s Health Sector Strategic Plan (HSSP), is a deliberate priority, a responsibility, and a significant opportunity for research. To guide this strategic direction, an assessment of MakCHS’s research grants and publication portfolio was conducted. Methods: A survey of all new and ongoing grants, as well as all publications, between January 2005 and December 2009 was conducted. Research, training, and education grants awarded to MakCHS’ constituent faculties and departments, were looked for through financial records at the college or by contact with funding organizations. Published manuscripts registered with PubMed, that included MakCHS faculty authors, were also analyzed. Results: A total of 58 active grants were identified, of which 18 had been initiated prior to 2005 and there were an average of about eight new grants per year. Most grants funded basic and applied research, with major focus areas being HIV/AIDS (44%), malaria (19%), maternal and child health (14%), tuberculosis (11%), mental health (3%), and others (8%). MakCHS faculty were identified as Principal Investigators (PIs) in only 22 (38%) active grants. Grant funding details were only available for one third of the active grants at MakCHS. A total of 837 publications were identified, with an average of 167 publications per year, most of which (66%) addressed the country’s priority health areas, and 58% had MakCHS faculty or students as first authors. Conclusions: The research grants and publications at MakCHS are generally well-aligned with the Ugandan Health Ministry priorities. Greater efforts to establish centralized and efficient grants management procedures are needed. In addition, greater efforts are needed to expand capacity for MakCHS faculty leadership of grants, as well as to continue to expand the contribution of MakCHS faculty to lead research publications.
Keywords: Makerere University College of Health Sciences; Health research capacity; Priorities